Sixty year of Indian industry (1947 to 2007): growth, reforms and outlook - Chatterjee, Anup (ed.) (New Delhi, 2006)
The present work traces the developments in Indian industry during the post-Independence period, explains the key reform measures undertaken for the development of industry in the wake of economic liberalisation and examines current issues pertaining to this vital sector of the Indian economy. The last decade of the 20th century was momentous in the economic history of India as it witnessed a successful transition of India from a controlled, inward looking, and slow growing economy to a liberalised and open economy that has now found a place amongst the fastest growing economies in the world.
Keywords: Indian industry - 1947 - 2007